2012
DOI: 10.2478/s11658-012-0021-8
|View full text |Cite
|
Sign up to set email alerts
|

Alterations of the Hsp70/Hsp90 chaperone and the HOP/CHIP co-chaperone system in cancer

Abstract: Activation of the Hsp90 chaperone system is a characteristic of cancer cells. The regulation of chaperone activities involves their interaction with cochaperones; therefore we investigated the expression of Hsp70 and Hsp90 and their specific co-chaperones HOP and CHIP in cancer cell lines and primary cancers. Inhibition of Hsp90 by 17AAG increased the levels of Hsp70, Hsp90 and HOP but not CHIP mRNA in cancer cells. These changes are linked to activation of the HSF1 transcription factor and we show that the HO… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
24
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(27 citation statements)
references
References 19 publications
2
24
1
Order By: Relevance
“…17 Two independent studies demonstrated elevated expression of HOP, with Hsp70 or Hsp90, in colon tumors. 18,19 High levels of these proteins have a negative impact on patient survival. 18,19 Elevated HOP expression has been observed in pancreatic and ovarian tumors and in hepatocellular carcinoma.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…17 Two independent studies demonstrated elevated expression of HOP, with Hsp70 or Hsp90, in colon tumors. 18,19 High levels of these proteins have a negative impact on patient survival. 18,19 Elevated HOP expression has been observed in pancreatic and ovarian tumors and in hepatocellular carcinoma.…”
Section: Introductionmentioning
confidence: 99%
“…18,19 High levels of these proteins have a negative impact on patient survival. 18,19 Elevated HOP expression has been observed in pancreatic and ovarian tumors and in hepatocellular carcinoma. [20][21][22] Secretion of HOP by GBM cells and other cancer cells is thought to influence cell proliferation, invasion and angiogenesis.…”
Section: Introductionmentioning
confidence: 99%
“…Although a supporting role for HSF1 in an oncogenic melodrama is attractive, a model for non-oncogene addiction with potentially greater ramifications for cancer treatment would argue that cancer cells experience high levels of proteotoxic stress and rely on stress response pathways for survival and proliferation. Cancer cells experience high levels of protein-modifying and metabolic stresses and seem to be particularly dependent on the various actions of HSP70/HSP90 for survival [97,98]. This phenomenon of non-oncogene addiction suggests that it may be possible to target such critical survival proteins for the development of therapies aimed at the selective killing of neoplastic cells.…”
Section: Non-oncogene Addiction In Inflammation-associated Cancersmentioning
confidence: 97%
“…Under oxidative stress conditions, STUB1 along with HSP70 appear to associate and colocalize with PARK7 in cells, indicating that noxious oxidative stimuli lead to PARK7 mitochondrial translocation in a chaperon-dependent manner (53). Modulations of the STUB1-HSP70 system have been observed both in cancer cell lines and primary cancers with possible implications in patient survival (77). In MPM, HSP70 is reported to be upregulated as part of an antiapoptotic, antistress response (27).…”
Section: Functional Enrichment Annotation Analysis Of Gene Ontologiesmentioning
confidence: 99%